2012
DOI: 10.1021/ie201472u
|View full text |Cite
|
Sign up to set email alerts
|

New Materials from Maleated Castor Oil/Epoxy Resin Blend Reinforced with Fly Ash

Abstract: Maleated castor oil (MACO) was prepared and blended with epoxy resin in 1:1 weight ratio. The prepared MACO-epoxy blend was characterized for its viscosity. Fly ash (10 wt %) was incorporated both in the 1:1 blend matrix as well as in the 100% epoxy resin matrix. Then curing was done by condensation polymerization reaction using 10 wt % of diethylene triamine (with respect to the total resin) in suitable reaction conditions. An interpenetrating cross-linked network was formed within the matrix between MACO and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…. XRD studies revealed that the 1 wt% nanoclays show better exfoliation within the matrix, and the cured DGEBA/ECO/C30B (8:2:0.1) system does not exhibit any diffraction peak in their spectra . It concluded that the nanocomposites synthesized using mechanical mixing followed by ultrasonication indicate that the nanoclays exfoliated within the DGEBA/ECO system.…”
Section: Resultsmentioning
confidence: 97%
“…. XRD studies revealed that the 1 wt% nanoclays show better exfoliation within the matrix, and the cured DGEBA/ECO/C30B (8:2:0.1) system does not exhibit any diffraction peak in their spectra . It concluded that the nanocomposites synthesized using mechanical mixing followed by ultrasonication indicate that the nanoclays exfoliated within the DGEBA/ECO system.…”
Section: Resultsmentioning
confidence: 97%
“…Regarding the tensile properties, a 74.6 times higher Young's modulus was reported for the 60:40 (modified oil-DCDP) composite containing 40 wt.% of glass fibers. Ray et al investigated the behavior of a blend of an epoxy resin and maleated castor oil co-reacted with an amine and filled with 10 wt% of fly ash [112].…”
Section: Compositementioning
confidence: 99%
“…This functionalization relatively increases the T g and improves the mechanical properties. 7 Maleation (maleination; reaction with MA) has been performed for CO via reaction of its hydroxyl groups and MA, 24,25 blending with other resins to achieve improved mechanical properties such as impact strength. 25 Generally, the VO and VE resins have low viscosity, low cost, and good pigment wetting properties, and produce relatively flexible coatings.…”
Section: Introductionmentioning
confidence: 99%